Corporate Governance Mechanisms and Possible Financial Statements Containing Fraud - Menik Indrati; Hermanto Hermanto; Eny Purwaningsih; Wulandari Agustinah; Aulia Sarikha (Budapest International Research and Critics University, 2021)
The aim of this study is to ascertain effect of Corporate Governance mechanisms on the possibility of financial statements containing fraud. This study examines the size of the board of commissioners as determined by the total number of board members in a company, the proportion of independent board members as determined by the proportion of an organization's board of directors that are independent as a percentage of the total number of board members, and board members with international experience. The audit committee's and worldwide audit's efficacy is evaluated by assigning a code one if all necessary information is released, a code two if Indonesia is informed but does not comply with the Code of Good Corporate Governance, and a code three if no information is provided. The Beneish M-Score measures financial statement fraud. The company indicated manipulator would be given code one if not indicated code 0. The company's size is quantified by the logarithm of the company's total assets in year t, leverage is measured by dividing total debt by total equity, and the company's age is estimated based on the number of years since the corporation was incorporated. On the Stock Exchange. A sample in this study of 100 non-financial companies listed on the Indonesia Stock Exchange in 2019. The statistical method used is binary logistics analysis. The findings of this study indicate that board size does not affect the likelihood of financial statements containing fraud; the proportion of independent board members does not affect the possibility of financial statements preventing fraud; board members with international experience do not affect the likelihood of financial statements preventing fraud.